2019
DOI: 10.2174/1874210601913010377
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of In-office Vital Tooth Whitening Combined with Different Concentrations of At-home Peroxides: A Randomized Double-blind Clinical Trial

Abstract: Background: The clinical evidence relate the effect of associating the in-office and at home vital tooth whitening, describing positive effects on tooth color change and reduction of dental sensitivity. Objective: The purpose of this randomized double-blind clinical trial was to evaluate the effect on the shortened application of in-office vital tooth whitening combined with different concentrations of at-home perox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 24 publications
0
7
0
1
Order By: Relevance
“…Detailed information regarding tooth whitening effectiveness in terms of color change could be found on the original RCT (17). Remove the tray and align it correctly over your teeth.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Detailed information regarding tooth whitening effectiveness in terms of color change could be found on the original RCT (17). Remove the tray and align it correctly over your teeth.…”
Section: Resultsmentioning
confidence: 99%
“…In this framework, Feliz-Matos et al reported the results of a randomized clinical trial (RCT), in 2018, where it was combined different concentrations of peroxides with the ambulatory and in-office VTW techniques. The research showed favourable outcomes in terms of tooth color change, dental sensitivity and length of the treatment (16,17). This has been one of the few recent studies that have evaluated the association of dental sensitivity with distinct percentages of the whitening agents employing the combined technique, because most of the authors have focused their investigations on the at-home or in-office techniques applied individually (18)(19)(20).…”
Section: Original Articlementioning
confidence: 94%
See 2 more Smart Citations
“…Ademais, o uso desse gel em baixas concentrações tem a vantagem de promover uma agressão reduzida a polpa, assim minimiza o risco e a intensidade de indução da sensibilidade dentinária(REZENDE et al, 2016). Já uma concentração maior do produto fornece resultados mais rápidos, porém promove sensibilidade dentinária numa intensidade de média a severa(FÉLIZ- MATOS et al, 2019).Além disso, Féliz-Matos et al (2019) mostraram que no clareamento caseiro há uma mudança de cor significativa independentemente da concentração utilizada, entre 10 a 20%. Outro importante ponto a ser analisado é a utilização do peróxido de hidrogênio em baixas concentrações em comparação ao uso de peróxido de carbamida no tratamento caseiro,Cardenas et al (2019) afirmaram que o branqueamento com peróxido de carbamida produz maior eficácia em termos de mudança de cor.…”
unclassified